Binding and Neutralization Antibody Titers After a Single Vaccine Dose in Health Care Workers Previously Infected With SARS-CoV-2 - Saadat, Saman (JAMA, 2021)
This study compares titers of binding and neutralizing antibodies after a single mRNA coronavirus vaccine dose in health care workers previously infected with SARS-CoV-2.